Prevalence, outcomes, and predictors of mortality among adult intensive care unit patients with sepsis at a Tertiary Hospital in Tanzania: A prospective cohort study - Atala Jongo; Edwin Lugazia; Salehe Mrutu; Amina Abillah Omari; Hassani Msanga; Ansbert Sweetbert Ndebea; Felix Paul Amani (PLoS ONE, 2026)
Background Sepsis continues to pose a significant global health challenge, particularly in low- and middle-income countries, which face a disproportionate burden of sepsis and sepsis-related deaths. The estimated prevalence of sepsis and sepsis-related mortality is higher in intensive care units than in hospitals overall. The burden can be higher in tertiary referral centers that receive patients from different regions. This study aimed to determine the prevalence of sepsis, its outcomes, and the factors associated with these outcomes among adult patients admitted to the Intensive Care Unit (ICU) of the Muhimbili National Hospital (MNH) in Tanzania. Methodology This prospective cohort study was conducted over a period of six months from May 16 to November 16, 2023, at MNH. A total of 248 patients were admitted during the study period and screened for sepsis on admission or for the development of sepsis during their ICU stay. Sepsis was defined according to the Sepsis-3 criteria as a suspected infection with a Sequential Organ Failure Assessment (SOFA) score ≥2 within 24 h of ICU admission. Proportions were used for descriptive statistics, and modified Poisson regression analysis was used to identify independent predictors of mortality at a 95% confidence interval, with P < 0.05 indicating statistical significance. Results The prevalence of sepsis was 41.5%. The respiratory system was the most common source of infection (32%), and 22.3% of patients had more than one infection site. The ICU mortality rate was 55.3%, with 35% of patients developing systemic complications during their ICU stay. Factors independently associated with mortality included multiple comorbidities (aPR 3.35, 95% confidence interval [CI], 1.20–9.32; p = 0.021) and a higher SOFA score (aPR 7.08, 95% CI 3.48–14.4; p < 0.001). Early initiation of antibiotics was independently associated with improved survival (aPR 0.47, 95% CI 0.27–0.84; p = 0.011). Conclusion This study revealed a high prevalence of sepsis and sepsis-related mortality in the ICU. A high SOFA score and multiple complications were independent predictors of mortality. Early initiation of antibiotic therapy was an independent predictor of survival. This underscores the importance of early treatment, close monitoring, and aggressive management in patients with predictors of poor outcome.